(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article delves into the lexical problems of translation, exploring the challenges translators face when bridging the linguistic and cultural gaps between languages. It highlights specific issues such as non-equivalence, polysemy, idiomatic expressions, cultural-specific terms, and false friends. By examining these challenges,